Estimasi Sumberdaya Batubara Menggunakan Metode Penampang dan Geostatistik Pada Area DDU Blok Timur Site Sungai Cuka, Kecamatan Kintap, Kabupaten Tanah Laut, Provinsi Kalimantan Selatan - Byma Bryanco; Dedi Yulhendra; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. PT. Britmindo is one of mining consultant company, and the centre office in Ragunan, South Jakarta. As aconsultant PT. Britmindo have a client is PT. Indoasia Cemerlang located in Sungai Cuka, Kintap, Region Tanah Laut, Province South Kalimantan. PT. Indoasia Cemerlang do exploration of coal in DDU Area East Block event have 27 bor hole. In this located didn’t do estimation coal of resources. And after do that can be know totality of tonnges and modle. Resources estimation is using two methods; there are ordinary kriging method and cross section method. Ordinary kriging method used if the thickness is unknown, and then to estimate the thickness number from an unknown block vertically or horizontally. The estimation result by using kriging method will configure modl from sediment and the total tonnage of coal.In located of research have 1 seam and that is seam A with split is A, A1, and A2. And total Estimation in cross section method in seam A is 60.979 tons coal tonnage, seam A1 is 21.236 tons coal tonnage, and seam A2 is 37.159 tons coal tonnage. With overburden from topo-top seam A is 77.103 bcm/tonne and interburden seam A2 is 48.414 bcm/tonne. Meanwhile in ordinary kriging method has a total tonnages in seam A is 499.590 tons coal tonnage, seam A1 is 244.530 tons coal tonnage, and seam A2 is 204.750 tons coal tonnage. And from this calculation we have length, volume and tonnages of coal.Keywords: coal, cross section, ordinary kriging, block model, resources